The impact of urban regeneration on transforming the image of a declining district: The case of the Bardo district in Constantine (Algeria) - Guerdouh Amal; Naceur Farida (Zbornik radova Departmana za geografiju, turizam i hotelijerstvo)
This article explores the urban regeneration project of an old, decaying district called Bardo, located in the city center of Constantine, Algeria, examining its impact on the physical transformation of the district and its image, as well as the reactions of the local population. The study focuses on the conversion of a former shantytown into an urban park, the beautification of the riverside area, and the resulting changes in the neighborhood's perception. The research utilizes a qualitative methodology, including interviews with stakeholders and analysis of historical and administrative documents. It finds that while the urban park has significantly enhanced the city's landscape and created a new public space, the project's focus on visual appeal has not fully addressed the underlying social and economic challenges faced by residents. The project's success in attracting tourism and investment comes at the expense of neglecting long-term community needs, raising concerns about the sustainability and equity of development. Ultimately, the study argues that urban regeneration projects must adopt a holistic approach that considers the social and economic needs of local communities, going beyond purely aesthetic transformations to create inclusive and equitable urban environments.